Efficacy of a dissolvable strip with calcium sodium phosphosilicate (NovaMin®) in providing rapid dentine hypersensitivity relief. (2019) - Gallob, John; Ling, Martin R.; Amini, Pejmon; Patil, Avinash; Atassi, Mounir
Abstract: Objective: To evaluate the efficacy of a dissolvable strip containing 15% w/w calcium sodium phosphosilicate (CSPS) (Novamin® ) in providing rapid relief from dentine hypersensitivity (DH). Methods: In this examiner-blind, proof-of-principle study, 120 healthy adults with DH were randomized 1:1 to the Test strip, professionally applied to facial surfaces of two selected teeth, or to No treatment. Sensitivity was assessed at baseline and 10 min, 2 h and 4 h post-application in response to evaporative (air) and tactile stimuli (measured by Schiff sensitivity scale/a numeric rating scale and tactile threshold, respectively). Change from baseline was analyzed by ANCOVA. Results: At 10 min post-application, mean Schiff score change from baseline (primary endpoint) was statistically significant with the Test strip (−0.46; 95% confidence intervals [CI]: −0.563, −0.356; p < 0.0001) but not with No treatment (−0.02; 95% CI: −0.119, 0.088; p = 0.7664). The between-treatment group difference favored the Test strip (difference: −0.44; 95% CI: −0.591, −0.297; p < 0.0001). Similar improvements with the Test strip were reported for all other evaporative (air) and tactile sensitivity endpoints (p < 0.0001 vs no-treatment) at all timepoints (10 min, 2 h, 4 h). Test strips were considered by most staff and participants slightly/moderately easy to apply (98%). Many participants rated the overall usage experience as "like moderately" (40%) or "like extremely" (20%). There were no treatment-related adverse events. Conclusion: This new CSPS-based technology may provide a novel treatment option for rapid relief from DH (Clinicaltrials.gov NCT02937623). Clinical significance: A dissolvable strip containing 15% w/w calcium sodium phosphosilicate (CSPS) demonstrated significantly greater dentine hypersensitivity reductions following a single application compared with no treatment. Strips were well-liked by participants and generally well tolerated. A strip containing CSPS, which dissolves within 10 min, may provide rapid relief from dentine hypersensitivity.